2022
DOI: 10.1038/s41531-022-00347-2
|View full text |Cite
|
Sign up to set email alerts
|

A review on pathology, mechanism, and therapy for cerebellum and tremor in Parkinson’s disease

Abstract: Tremor is one of the core symptoms of Parkinson’s disease (PD), but its mechanism is poorly understood. The cerebellum is a growing focus in PD-related researches and is reported to play an important role in tremor in PD. The cerebellum may participate in the modulation of tremor amplitude via cerebello-thalamo-cortical circuits. The cerebellar excitatory projections to the ventral intermediate nucleus of the thalamus may be enhanced due to PD-related changes, including dopaminergic/non-dopaminergic system abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 123 publications
2
13
1
Order By: Relevance
“…Due to striatal dopamine deficiency, PD presents with dyskinesias, including impaired range and speed of movement, limb stiffness, or resting tremors. 218 Dopaminergic neurons in PD often exhibit Lewy bodies, in which there is massive accumulation of α-synuclein (αsyn) in the cytoplasm. 218 In PD patients, α-syn aggregation is widely regarded as a major causative factor.…”
Section: Pathogenic and Regulatory Mechanisms Of Aging-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to striatal dopamine deficiency, PD presents with dyskinesias, including impaired range and speed of movement, limb stiffness, or resting tremors. 218 Dopaminergic neurons in PD often exhibit Lewy bodies, in which there is massive accumulation of α-synuclein (αsyn) in the cytoplasm. 218 In PD patients, α-syn aggregation is widely regarded as a major causative factor.…”
Section: Pathogenic and Regulatory Mechanisms Of Aging-related Diseasesmentioning
confidence: 99%
“…218 Dopaminergic neurons in PD often exhibit Lewy bodies, in which there is massive accumulation of α-synuclein (αsyn) in the cytoplasm. 218 In PD patients, α-syn aggregation is widely regarded as a major causative factor. α-Syn oligomers form large, insoluble, neurotoxic fibrils called Lewy bodies.…”
Section: Pathogenic and Regulatory Mechanisms Of Aging-related Diseasesmentioning
confidence: 99%
“…The cerebellum is involved in numerous functions (Stoodley and Schmahmann, 2010;Buckner, 2013;Steele et al, 2017), such as motor control, emotional processing, working memory. By means of PET-CT, fMRI and structural MRI, researchers have found that there are metabolic, functional as well as structural alterations in the cerebellum of PD patients and such alterations are associated with the production of motor and non-motor symptoms of PD (Wu and Hallett, 2013;Haghshomar et al, 2022;Zhong et al, 2022), especially tremor and cognitive impairment. A PET-based study revealed a tremor-related metabolic network in PD which showed increased activity of the cerebellum, primary motor cortex and caudate/putamen and correlated significantly and positively with clinical ratings of tremor.…”
Section: Increased Functional Connectivity Within the Sensorimotor Ne...mentioning
confidence: 99%
“…Alpha synuclein formed Lewy bodies have been found in the Bergmann glia and Purkinje cell axons in the cerebellum. Also, in PD patients, there is a presence of increased climbing fiber-Purkinje cell synapses as well as the presence of torpedoes in Purkinje cell axons demonstrating cerebellar involvement in PD [26,27].…”
Section: Cerebellar Involvement In Ataxia Tremor and Dystoniamentioning
confidence: 99%